Conceptualisation of postnatal depression in Malaysia: the contribution of critical realism in exploring the understanding of women’s and healthcare practitioners’ perspectives = Conceptualización de la depresión posnatal en Malasia: la contribución Del realismo crítico en la exploración de la comprensión de las perspectivas de las mujeres y los profesionales de la salud - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (Universidad del Zulia, 2020)
This study aimed to explore the perception of PND in women and healthcare practitioners (HCPs) in Malaysia using critical realism. This qualitative study was conducted among 33 Malaysian women attending child or postnatal care and 18 healthcare practitioners (HCPs) using face-to-face semi-structured interviews in six selected maternal and child health clinics and a female psychiatric ward in Kuala Lumpur, Malaysia. The findings suggest that the women’s and HCPs’ conceptualisations of PND are not entirely established based on either scientific or professional expertise, indicating that there is a lack of systematic awareness of PND within the Malaysian healthcare setting. ************************************************************************** Este estudio tuvo como objetivo explorar la percepción de PND en mujeres y profesionales de la salud (HCP) en Malasia utilizando realismo crítico. Este estudio cualitativo se realizó entre 33 mujeres malasias que asistieron a atención infantil o postnatal y 18 profesionales de la salud (HCP) utilizando entrevistas semiestructuradas cara a cara en seis clínicas de salud materna e infantil seleccionadas y una sala de psiquiatría femenina en Kuala Lumpur, Malasia. Los hallazgos sugieren que las conceptualizaciones de PND de las mujeres y los profesionales de la salud no están completamente establecidas en base a la experiencia científica o profesional, lo que indica que existe una falta de conocimiento sistemático de PND dentro del entorno de atención médica de Malasia.